2000
DOI: 10.4049/jimmunol.164.10.5499
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire Requirements of CD4+ T Cells That Prevent Spontaneous Autoimmune Encephalomyelitis

Abstract: Spontaneous experimental autoimmune encephalomyelitis arises in 100% of mice exclusively harboring myelin basic protein-specific T cells, and can be prevented by a single injection of CD4+ T cells obtained from normal donors. Given the powerful regulatory effect of the transferred T cells, we further investigated their properties, and, in particular, their repertoire requirements. Transfer of monoclonal OVA-specific CD4+ T cells did not confer protection from disease even when present at very high proportions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 66 publications
(85 reference statements)
6
74
0
2
Order By: Relevance
“…However, there is increasing evidence that regulatory CD4 T cells exist in the CD25 Ϫ compartment as well (35,36). Our data showing the capacity of the CD25 Ϫ FIGURE 6.…”
Section: Discussionmentioning
confidence: 75%
“…However, there is increasing evidence that regulatory CD4 T cells exist in the CD25 Ϫ compartment as well (35,36). Our data showing the capacity of the CD25 Ϫ FIGURE 6.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, it appears that the normal immune repertoire is composed of potentially autoreactive Th as well as inhibitory T cells (Fig. 4C) (35,42,43) and inhibitory T cells expand whenever there is an impending danger of pathologic autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Only a ␣␤ ϩ T cell population possessed effective regulatory activity. Additional studies have shown that the regulatory cells that prevent spontaneous EAE in this model are CD4 ϩ T cells expressing a diverse T cell repertoire (27).…”
Section: Discussionmentioning
confidence: 99%